FAKTOR - FAKTOR YANG MEMPENGARUHI PERMINTAAN CABAI BESAR (Capsicum annum L) PADA TINGKAT RUMAH TANGGA DI KOTA PONTIANAK - SUPRAPTI, GUSNI; DOLOROSA, EVA; IMELDA, IMELDA (Jurnal Sains Mahasiswa Pertanian, 2018)
This study aims to analyze factors that affect demand of red pepper and to analyze the elasticity of demand for prices in Pontianak city. This study was conducted in Pontianak traditional market ie Dahlia Market, Flamboyan Market, Kemuning Market and Teratai Market. There were 100 respondent which has been determined purposively. The data were analyzed by using the transformed multiple regression analysis with an SPSS software program. Independent variables are price of red pepper, price of red onion, frequency of purchase, income of household. The result showed factors that significantly affect the demand of red pepper is price of red pepper, frequency of purchase and income of household, while price of red onion is not affect to demand of red pepper. The elasticity of demand for the price of red peppers is inelastic, meaning the percentage change in quantity demanded is less than the price change. Cross-price elasticity of demand is positive to shows that red union is not complement commodity. Income elasticity of demand is negative to shows that red pepperas an inferiorcommodity.Â